A better world in 2020: wake-up calls from the next generation - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
In preparation for its international conference on "Sustainable Food Security For All By 2020," taking place in Bonn, Germany, in September 2001, IFPRI’s 2020 Vision Initiative invited young people from around the world to show us in pictures and words how they saw our world in 2020. We asked them what we should do to assure a better world for all. We thank the more than 600 youngsters from about two dozen countries who participated in the poster and essay competitions and shared their creativity, insights, and aspirations. They demonstrated a very personal commitment to making a better world for all in 2020 and are an inspiration to us all. This booklet contains the winning posters and essays as well as other compelling results from the competitions. We have included excerpts from other submissions in order to share a wide range of perspectives. We invite you to view and read the anxieties, aspirations, visions, and expectations of the next generation.